The impact of COVID-19 on child welfare-involved families: Implications for parent–child reunification and child welfare professionals. (September 2021) - Goldberg, Abbie E.; Brodzinsky, David; Singer, Jacqueline; Crozier, Patience
The COVID-19 pandemic has impacted children and parents involved in the child welfare system and the professionals working with these families. Using survey data collected August–September of 2020, this mixed-methods study examined the perspectives of 196 child welfare-involved professionals (77 attorneys, 99 caseworkers, and 20 therapists) in the United States about the impact of COVID-19 on parents of origin, children, foster parents, and child welfare professionals. Particular attention was paid to the implications of COVID-19 and associated challenges for parent–child contact and reunification. With respect to professional stresses, more than half of participants worried about their own personal safety and health amidst COVID-19, and more than three-quarters expressed concerns about the safety and well-being of child welfare-involved families. Participants, especially attorneys, expressed concerns about parent–child contact and disruptions to reunification. In-person parent–child visits had all but ceased during the early part of the pandemic, and participants identified barriers to effective virtual visits, including lack of foster parent oversight, technology issues, and children's developmental stage and/or lack of engagement. Attorneys were especially critical of the cessation of in-person visits and viewed this as a serious threat to child-parent bonds and reunification. Participants, especially child welfare workers, voiced concerns about children's mental health and educational outcomes amidst the pandemic. Findings have implications for attorneys, child welfare workers, and other practitioners who directly and indirectly interface with child welfare-involved families.